Pengaruh Penyuluhan Phbs Tentang Mencuci Tangan Terhadap Perilaku Siswa Kelas V di SD N 116240 Kampung dalam Kecamatan Bilah Hulu Kabupaten Labuhan Batu Tahun 2018 - Yunizar, Aida; Harahap, Yanna Wari (Jurnal Kesehatan Ilmiah Aufa Royhan, 2019)
Behavior Clean and Healthy (PHBS) is all health behavior that is done on the awareness so that family members or family can help themselves in the field of health. The purpose of this study was to determine the influence of PHBS Counseling on Hand Washing Against Student Behavior of Class V in SD N 116240 Kampung Dalam Subdistrict Bilah Hulu Labuhan Batu Regency Year 2018. This research method is quasi experiment or Quasi Experimental. By using the design of One Group Pretest and Posttest Design to know the effect of PHBS counseling about hand washing to the behavior of grade V students at SD Negeri 116240 Kampung Dalam Subdistrict Bilah Huluh Labuhan Batu District Year 2018. Based on the result of the research, it can be concluded that there is a significant correlation between knowledge (p = 0.000), attitude (p = 0,000) and action (p = 0,000) to the behavior of class V students who show the clean and healthy life behavior with less category. It is hoped that SD family should always instill the values of PHBS to the elementary school children to prevent the coming of the disease and also conduct health checks periodically and at the same time provide information about PHBS.